A Spanner in the Works: Human–Elephant Conflict Complicates the Food–Water–Energy Nexus in Drylands of Africa - Githiru, Mwangi; Mutwiwa, Urbanus; Kasaine, Simon; Schulte, Bruce (Frontiers in Environmental Science, 2017)
The two major conservation issues for drylands of Africa are habitat loss or degradation and habitat fragmentation, largely from agriculture, charcoal production, and infrastructural development. A key question for management is how these landscapes can retain their critical ecological functions and services, while simultaneously supporting resilient livelihoods. It is a clear nexus question involving food (agriculture), water and energy (fuelwood), which is complicated by human-wildlife conflicts. While these could appear disparate issues, they are closely connected in dryland forest landscapes of Africa where elephants occur close to areas of human habitation. For instance, crop failure, whether due to weather or wildlife damage, is a key driver for rural farmers seeking alternative livelihoods and incomes, one of the commonest being charcoal production. Similarly, heavy reliance on wood-based energy often leads to degradation of wildlife habitat, which heightens competition with wildlife for food and water, increasing the possibility of crop-raiding. So, for multifunctional landscapes where elephants occur in close proximity with humans, any food-water-energy nexus activities towards achieving sustainability and resilience should consider human-elephant conflicts. Here, we broach these food-water-energy nexus issues with a focus on dryland areas of Africa and human-elephant conflicts. We highlight an ongoing study attempting to address this nexus holistically by employing a climate-smart agriculture and agro-forestry based design, augmented by an elephant deterrent study and an eco-charcoal production venture.